2004
DOI: 10.1073/pnas.0402822101
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic expression of Galα1-4Gal on avian glycoproteins: Glycan differentiation inscribed in the early history of modern birds

Abstract: Glycoproteins containing Gal␣1-4Gal (galabiose) had been rarely found in vertebrates, except in a few species of birds and amphibians. We had previously reported that pigeon (Columba livia) egg white and serum glycoproteins are rich in N-glycans with Gal␣1-4Gal at nonreducing termini. To investigate the origin of Gal␣1-4Gal expression in avian evolution, we examined the presence of Gal␣1-4Gal glycoproteins in egg whites from 20 orders, 88 families, 163 genera, and 181 species of birds, as probed by Western blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
42
2

Year Published

2006
2006
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 53 publications
7
42
2
Order By: Relevance
“…Recent molecular and morphological studies have yielded a consensus that the basal split among extant birds resides between palaeognath (ratites and tinamous) and neognaths (all other extant birds) (Cracraft, 1988(Cracraft, , 2001Cracraft and Mindell, 1989;Livezey and Zusi, 2001;van Tuinen et al, 2000;Edwards et al, 2002;Garcia-Moreno et al, 2003;Sorenson et al, 2003;Chubb, 2004;Cracraft et al, 2004;Fain and Houde, 2004;Harrison et al, 2004;Suzuki et al, 2004). This basal divergence in the avian tree is now well established, but the higher-order relationships and those among orders of neognaths birds remain unclear even among recent molecular studies, necessitating a reexamination of the phylogeny by including data from diverse bird species.…”
Section: Introductionmentioning
confidence: 97%
“…Recent molecular and morphological studies have yielded a consensus that the basal split among extant birds resides between palaeognath (ratites and tinamous) and neognaths (all other extant birds) (Cracraft, 1988(Cracraft, , 2001Cracraft and Mindell, 1989;Livezey and Zusi, 2001;van Tuinen et al, 2000;Edwards et al, 2002;Garcia-Moreno et al, 2003;Sorenson et al, 2003;Chubb, 2004;Cracraft et al, 2004;Fain and Houde, 2004;Harrison et al, 2004;Suzuki et al, 2004). This basal divergence in the avian tree is now well established, but the higher-order relationships and those among orders of neognaths birds remain unclear even among recent molecular studies, necessitating a reexamination of the phylogeny by including data from diverse bird species.…”
Section: Introductionmentioning
confidence: 97%
“…However, we found that the expression of Gal␣1-4Gal on glycoproteins is correlated with the avian phylogeny (8). To investigate the enzyme catalyzing the formation of Gal␣1-4Gal on glycoproteins, we successfully isolated the cDNA encoding pigeon ␣4GalT(Gal), which had not been identified previously.…”
Section: Pigeon ␣4galt(gal) Possesses Distinct Substrate Preferences mentioning
confidence: 99%
“…This result corresponds to the close evolutionary relationship within Galloanserae according to the absent of Gal 1-4Gal in all tested glycoproteins of Galloanserae EW. 25) In addition, the relationship of meleagrin with ''similar to meleagrin,'' from the same order (Galliformes), is closer than with cygnin or dBPS 2 , from the different order (Anseriformes). A close relationship within Galliformes order than with other from Anseriformes order was also suggested in ovotransferrin.…”
Section: Discussionmentioning
confidence: 97%